Ligand-Free Copper-Catalyzed Borylation of Aryl and Benzyl Halides with Bis(pinacolato)diboron - Yan, Guobing; Yang, MingHua; Yu, Jian (Letters in Organic Chemistry, 2012)
The CuBr-catalyzed cross-coupling reaction of aryl iodides with B2pin2 in the absence of ligand has been developed for the preparation of arylboronates. The reaction was also suitable for the borylation of aryl bromides and benzyl halides, albeit in moderate yields.
Keywords: Aryl and benzyl halides